Evaluation of neopterin level and disease severity in patients with psoriasis vulgaris treated with narrowband UVB - Funda Kemeriz; Müzeyyen Gönül; Fatma Pelin Cengiz; Nazan Emiroğlu; Bengü Çevirğen Cemil (Wolters Kluwer Medknow Publications, 2019)
Background: Neopterin is a biochemical marker of cellular immunity. It has been reported that serum and urine neopterin levels increase in psoriasis and decrease with treatment. Nevertheless, assessment of a direct link between narrowband ultraviolet B (UVB) therapy and neopterin level in association with Psoriasis Area and Severity Index (PASI) scores has not been performed yet. We aimed to evaluate the serum neopterin level in patients with psoriasis treated with narrowband UVB therapy in association with disease severity. Materials and Methods: The study included 35 patients with chronic plaque-type psoriasis who had PASI scores of >10 or below 10 but resistant to topical therapies and 30 healthy individuals. The narrowband UVB therapy was administered to the patient group (n = 35). Serum neopterin analysis was performed with an enzyme-linked immunosorbent assay method before and after treatment. Results: There was statistically significant correlation between neopterin level and PASI score in the patient group (P = 0.011). The serum neopterin level was significantly increased in patients with higher PASI score. Moreover, the serum neopterin level was found to be statistically higher in severe psoriasis group (PASI score ≥10, n = 14) than the mild-moderate group (PASI score <10, n = 21) (P = 0.001). Furthermore, a significant decrease was observed according to serum neopterin level after the narrowband UVB therapy in the remaining 20 patients who were able to comply with the scheduled therapy and follow-up procedure (P = 0.026). Conclusion: Serum neopterin levels were found to be an useful marker for evaluating disease severity and efficacy of narrowband UVB treatment. Thus, our findings may provide a new approach with the management of disease and follow-up strategies in patients with psoriasis.